2022
DOI: 10.1177/09576509221116503
|View full text |Cite
|
Sign up to set email alerts
|

CFD modelling on flow field characteristics of engine cooling water jacket and its cooling performance improvement based on coolant transport path analysis method

Abstract: Reasonable coolant flow distribution and its heat transfer coefficient (HTC) distribution are of great significance to the cooling performance of water-cooled engine. Therefore, the present paper proposes a coolant transport path analysis method aiming at analyzing coolant velocity distribution and optimizing the coolant flow characteristics of water jacket based on Computational Fluid Dynamics (CFD), with particular emphasis on the assessment of coolant flow velocity distributions of high-temperature area of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Germanium material was used as the solar cell, while aluminium was used as the cooling pad material. A combination of the laminar model corresponding to a Reynolds number (Re) of 1482.41 at 0.5 L/m and an enhanced wall function K-ε model corresponding to 1-2.5 L/m with an increase in Re from 1482.41 to 8372.26 was used and adapted, as described in [97][98][99][100][101]. A 10 −6 residual was considered to indicate a converged solution.…”
Section: Novel Approach To Cpv Coolingmentioning
confidence: 99%
“…Germanium material was used as the solar cell, while aluminium was used as the cooling pad material. A combination of the laminar model corresponding to a Reynolds number (Re) of 1482.41 at 0.5 L/m and an enhanced wall function K-ε model corresponding to 1-2.5 L/m with an increase in Re from 1482.41 to 8372.26 was used and adapted, as described in [97][98][99][100][101]. A 10 −6 residual was considered to indicate a converged solution.…”
Section: Novel Approach To Cpv Coolingmentioning
confidence: 99%
“…Several scholars have conducted extensive research on cooling water flow in this context. Tan et al [3] examined the impact of cooling water flow distribution and heat transfer coefficient distribution on the cooling efficiency of water-cooled engines.. The results show that analyzing the cooling water delivery path to optimize the flow properties of the water jacket cooling water is an effective method for achieving more reasonable cooling water flow distribution.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Ankit et al [10] used ANSYS/Fluent to simulate stable flow conditions and reduced thermal gradients on the piston liner wall in a one-to-one replicated diesel engine water jacket geometry. Tan et al [11] examined the distribution of heat transfer coefficients (HTC) in a single-cylinder water jacket under different flow rates of coolant (15 L/min, 25 L/min, 35 L/min) using ANSYS/Fluent software. Regardless of the flow rates, they observed that the HTC distribution had a small area reaching up to 5000 W/(m 2 K).…”
Section: Introductionmentioning
confidence: 99%